Public Event: David Barsamian on Corporate Media, Alternative media, and Democracy - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2015)
(Post on behalf of Prof. Robert Hackett) There will be a public seminar by David Barsamian, the founder and director of Alternative Radio. The seminar will take place on November 4, 2015, starting at 1.30 p.m. in the CMNS Conference Room K8652 at Burnaby Campus. Please see the attached poster for details.